The Age or Excess of the MGinf Queue Busy Cycle Mean Value - Ferreira, M. A. M. (arXiv:2110.06374, 2025)
In this work, approximate and exact results concerning a performance measure of the MGinf system, the age or the excess of the busy cycle, are presented. It will be seen that it is also a measure of the busy period performance. Service distributions for which it is given for a simple expression and others for which this does not happen are considered. For this last case, bounds are deduced. A special emphasis is given to the exponential distribution and to those related with it, useful in reliability theory.